Pengaruh Motivasi Terhadap Kinerja Pegawai Negeri Sipil Pada Dinas Kearsipan dan Perpustakaan Daerah Kabupaten Paser - Dedy Darmawan; Istiana Agustika Anandy; Amir Hamzah; Ismail Ismail; Shalahuddin (Pusat Riset dan Inovasi Nasional, 2021)
The study uses a quantitative data analysis approach used with SPSS. The sample in the study was 36 people. The purpose of this study is 1). To analyze the influence of motivation consisting of physiologic needs, security needs, social needs, reward needs, and self-actualization needs have simultaneous and partial influences on Employee Performance 2). To analyze the motivation variables studied, which are between physiologic needs, security needs, social needs, reward needs, and the dominant self-actualization needs for Employee Performance. The results showed that: 1). Simultaneously and partially a strong relationship between motivational variables consisting of physiologic needs, security needs, social needs, reward needs, and self-actualization needs with the performance of Civil Servants in the Archivist Office and Paser District Library. 2). Partial test results showed that social needs exerted a dominant influence, evidenced by a calculated value of 2,414 greater than other variables.